Utilization of Mango (Mangifera indica L.variety Chok Anan peel.A Nen generation fibre ingredient In bread. - Abdul Aziz, Noor Aziah (Universiti Sains Malaysia, 2012)

(untitled)
The objective of this research was to evaluate the physical, nutritional and sensory attributes of composite flour breads. Substitutions of mango peel flour (MPF) with white bread flour were carried out at 5%, 10% and 15% levels. Physico-chemical and functional properties of both fresh mango peel (FMP) and peel flour were also determined.